John Gardner - McWilliams, Dean. (Boston : Twayne Publishers, 1990)
A study of the novels of American author John Gardner, examining his work independently of the "moral theory" posed by Gardner in his 1978 book-length critical statement "On Moral Fiction," in which he managed to offend virtually everyone of consequence in contemporary American fiction.
Includes bibliographical references (p. 128-130).
Adult
Keywords: Gardner, John, -- 1933- -- Criticism and interpretation; Gardner, John, -- 1933- -- Criticism, interpretation, etc